Proteinase 3-ANCA Vasculitis versus Myeloperoxidase-ANCA Vasculitis - Hilhorst, Marc (J Am Soc Nephrol, 2015)
In patients with GN or vasculitis, ANCAs are directed against proteinase 3 (PR3) or myeloperoxidase (MPO). The differences between PR3-ANCA-associated vasculitis (AAV) and MPO-AAV described in the past have been supplemented during the last decade. In this review, we discuss the differences between these two small-vessel vasculitides, focusing especially on possible etiologic and pathophysiologic differences. PR3-AAV is more common in northern parts of the world, whereas MPO-AAV is more common in southern regions of Europe, Asia, and the Pacific, with the exception of New Zealand and Australia. A genetic contribution has been extensively studied, and there is a high prevalence of the HLA-DPB1*04:01 allele in patients with PR3-AAV as opposed to patients with MPO-AAV and/or healthy controls. Histologically, MPO-AAV and PR3-AAV are similar but show qualitative differences when analyzed carefully. Clinically, both serotypes are difficult to distinguish, but quantitative differences are present. More organs are affected in PR3-AAV, whereas renal limited vasculitis occurs more often in patients with MPO-AAV. For future clinical trials, we advocate classifying patients by ANCA serotype as opposed to the traditional disease type classification.